Advancements in the treatment of mycosis fungoides and Sézary syndrome: monoclonal antibodies, immunotherapies, and Janus kinase inhibitors - Quadri, Iman; Reneau, John C.; Hanel, Walter; Chung, Catherine G. (Frontiers in Immunology, 2023)
Mycosis fungoides (MF) and Sézary syndrome (SS) are forms of cutaneous T cell lymphoma (CTCL) that pose significant challenges in their clinical management, par]cularly in refractory and advanced-stage disease. With the emergence of novel therapeu]c modali]es however, there are increasing opportuni]es to exploit the current understanding of pathophysiologic mechanisms of MF/SS for treatment. This review summarizes recent advances in the treatment of MF/SS, with a focus on monoclonal an]bodies, immunotherapies, and Janus kinase (JAK) inhibitors, including ongoing clinical trials.